(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article reveals the orientation of educational values ​​to the social and personal factor. Social values, including educational values, serve to form a person, increase his value, ensure recognition by pedagogues of the individual factor as the leading subject of educational processes, in which free and independent thinking, as well as social it is desirable that it helps to form activity skills.